2002
DOI: 10.1084/jem.20020205
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role for the C5a Receptor in Regulating the Effector Phase of Synovial Infiltration and Joint Destruction in Experimental Arthritis

Abstract: A characteristic feature of rheumatoid arthritis is the abundance of inflammatory cells in the diseased joint. Two major components of this infiltrate are neutrophils in the synovial fluid and macrophages in the synovial tissue. These cells produce cytokines including tumor necrosis factor α and other proinflammatory mediators that likely drive the disease through its effector phases. To investigate what mechanisms underlie the recruitment of these cells into the synovial fluid and tissue, we performed express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
111
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(120 citation statements)
references
References 39 publications
(43 reference statements)
5
111
2
Order By: Relevance
“…Recent studies in mice deficient in members of the complement system have 2546 LI ET AL shown that both alternative and classical pathways of complement activation are important in the development of arthritis in CIA as well as in CII antibodyinduced arthritis (36)(37)(38). Provided that plasmin plays an essential role in complement activation, these findings are consistent with our results in plasminogen-deficient mice in CIA.…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies in mice deficient in members of the complement system have 2546 LI ET AL shown that both alternative and classical pathways of complement activation are important in the development of arthritis in CIA as well as in CII antibodyinduced arthritis (36)(37)(38). Provided that plasmin plays an essential role in complement activation, these findings are consistent with our results in plasminogen-deficient mice in CIA.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, it has been shown that the C5a receptor plays a critical role in the effector phase of synovial infiltration and joint destruction [27]. To assess the importance of the early components of complement activation for the antibody-mediated effector phase of arthritis, we used arthritogenic monoclonal antibodies to CII [8,14] to induce arthritis in C3 -/-, FB -/-, and control DBA/1J mice.…”
Section: Discussionmentioning
confidence: 99%
“…VCAM-1 was reduced in DTHA paws following anti-C5aR treatment, and as C5aR is expressed on endothelial cells and synovial fibroblasts [7] this reduction in VCAM-1 could represent a direct effect of anti-C5aR treatment on these cells. In support of this, it has been shown that C5aR À/À mice have lower expression of VCAM-1 mRNA than wild-type mice after induction of CAIA [19].…”
Section: Discussionmentioning
confidence: 62%
“…Complement activation and C5a production in DTHA most likely takes place at the cartilage surfaces where the anti-CII administered during induction localises and forms immune complexes with cartilage CII. In the CAIA and CIA models anti-CII antibodies deposit on cartilage surfaces and activate complement [19,33], and in the K/BxN and K/BxN serum transfer models glucose-6-phosphate isomerase (GPI)-anti-GPI immune complexes deposit on the cartilage surfaces and activate complement [34]. Cartilage surfaces are not very rich in cells and thus lack the cell membrane-bound C3 inactivators decay-acceleration factor (DAF) and membrane cofactor protein (MCP), so only soluble inhibitors and surface sialic acid residues are present to dampen the activation of complement pathways [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation